Corrosion-resistant rolled clad steel plate for medium-temperature equipment and manufacturing method of corrosion-resistant rolled clad steel plate

By forming a stable MC precipitation phase in the base carbon steel of the rolled composite steel plate and fixing the carbon element, the problem of degradation of stainless steel corrosion resistance caused by carbon element diffusion is solved, and the corrosion resistance and safety performance of the steel plate is significantly improved.

CN119913429APending Publication Date: 2025-05-02BAOSHAN IRON & STEEL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311425065.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Under high temperature conditions, the carbon elements in the base carbon steel diffuse to the composite material through the interface, resulting in the reduction of the corrosion resistance of stainless steel and poses safety hazards.

Method used

By forming a large number of fine diffusion distributions and stable high-temperature performance in the base carbon steel, the carbon elements in the steel are fixed to prevent them from diffusing to the composite material interface.

Benefits of technology

Effectively block or reduce the diffusion of carbon elements, reduce the risk of intergranular corrosion of stainless steel, and improve the corrosion resistance and safety performance of rolled composite steel plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant rolled composite steel plate for medium-temperature equipment and a manufacturing method of the corrosion-resistant rolled composite steel plate. The composite steel plate comprises a base material, a composite layer and a transition layer between the base material and the composite layer, the base material is prepared from, by weight, 0.01%-0.15% of C, 0.2%-0.7% of Si, 0.1%-1.70% of Mn, 0.006%-0.025% of Ti, 0.004%-0.015% of Als, 0.0010%-0.050% of Nb, 0.15%-0.50% of V, 0.0005%-0.0050% of B, 0.0015%-0.0050% of N, smaller than or equal to 0.0165% of P, smaller than or equal to 0.010% of S, smaller than or equal to 0.005% of O and the balance Fe and other inevitable impurities. By blocking or reducing diffusion of carbon elements on the base material carbon steel side at the interface of the composite steel plate, the possibility of failure caused by intergranular corrosion of stainless steel on the composite layer side is reduced, the corrosion resistance and safety performance of the rolled composite steel plate are comprehensively improved, and the composite steel plate is suitable for 300-450 DEG C medium-temperature equipment in the field of energy manufacturing of petroleum refining, coal chemical industry and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to corrosion-resistant steel and a method for making the same, and in particular to a corrosion-resistant rolled composite steel plate for medium-temperature equipment and a method for making the same, which is suitable for medium-temperature equipment at 300-450°C in energy manufacturing fields such as petroleum refining and coal chemical industry. Background Art

[0002] Composite steel plates made of low alloy steel + various corrosion-resistant materials are often used in crude oil processing, energy and chemical industries because of their high mechanical strength and strong corrosion resistance. With the rapid development of the national economy, there is an increasing demand for various energy-related raw materials such as oil and fertilizers. In order to improve energy production efficiency, it is imperative to make energy production and processing equipment large-scale, high-parameter (higher temperature, higher pressure) and lightweight. This equipment upgrade demand puts higher requirements on the performance of steel plates for manufacturing equipment, that is, it requires such steel plates to have not only higher strength and hardness, but also excellent toughness, processing and forming performance, and better corrosion resistance.

[0003] The production process of traditional composite steel plates is the explosive composite process. The main problem of this production process is that when explosives are used for explosive composite, a large amount of harmful gases will be generated, which will have an adverse impact on the environment. That is, this type of production process does not meet environmental protection requirements; at the same time, the bonding rate at the interface of the explosive composite steel plate is low, and sometimes it cannot meet the bonding rate requirement of more than 97%. If this type of steel plate is used to manufacture various high-temperature, high-pressure, and large-scale container equipment, there will be a great safety hazard. Once the composite steel plate joint is separated and the equipment fails, it will have a huge impact on the safety of life and property.

[0004] Compared with explosive composite steel plates, the bonding rate of rolled composite steel plates is greatly improved to more than 99%, and the production process is more environmentally friendly than explosive composite steel plates. Therefore, in recent years, the production scale of rolled composite steel plates and the use of engineering projects have been expanding year by year.

[0005] However, whether it is explosive composite steel plate or rolled composite steel plate, a certain transition layer will be produced at the interface between carbon steel and other corrosion-resistant materials. The composition of the transition layer is relatively complex, especially when working for a long time under medium temperature conditions of 300-450℃, the alloy elements in the base carbon steel will migrate and diffuse to the composite material through the transition layer, causing the microstructure of the corrosion-resistant material to change, thereby adversely affecting the corrosion resistance of the composite corrosion-resistant material.

[0006] Therefore, how to reasonably design the alloy composition and production process of the carbon steel base layer, control the microstructure and precipitation phase of the carbon steel material, minimize the diffusion behavior of elements in the base carbon steel material, especially the carbon element, under long-term high temperature conditions, and avoid the negative impact of intergranular corrosion of stainless steel caused by the increase of carbon elements in the corrosion-resistant material and the formation of a large amount of carbides, which leads to a decrease in the corrosion resistance of stainless steel, has become an urgent requirement for improving the comprehensive performance of rolled composite steel plates.

[0007] Existing technologies such as: Chinese patent publication number CN103934266A discloses "a method for preparing a copper / aluminum composite strip with reduced interface layer thickness". The invention uses soft T2 copper strip as copper raw material; uses soft aluminum-silicon alloy strip with silicon mass percentage of 3.25-8.89% as silicon-aluminum alloy raw material; the thickness ratio of copper raw material to silicon-aluminum alloy raw material is 1:1; rolling and compounding is performed to form a rolled composite strip; then, diffusion heat treatment is performed, and the temperature is raised to 200-400°C under inert gas protection conditions, kept warm for 0.5-2h, and cooled to room temperature with the furnace; the main purpose of the method of the invention is to obtain a copper / aluminum composite strip with high dimensional accuracy, small composite interface size, firm bonding, and good surface quality while ensuring 50% copper material savings. Since the materials in the invention are pure copper and aluminum-silicon alloy, the properties of these two metals are very different from those of low-alloy steel and stainless steel, so the method for reducing the thickness of the interface layer involved in the patent is not very suitable for rolling composite steel plates of low-alloy steel and stainless steel.

[0008] Chinese patent publication number CN108116006A discloses "a super austenitic stainless steel rolled composite steel plate and its manufacturing method". In this patent, the inventor assembled carbon steel and austenitic stainless steel slabs and then rolled them. Finally, a rolled composite steel plate material of carbon steel base layer + austenitic cladding was obtained. However, the materials disclosed in this patent do not involve the influence of element diffusion at the interface on the corrosion resistance of the composite material.

[0009] Chinese patent publication number CN108085585A discloses "a high-strength corrosion-resistant composite patterned steel and its manufacturing method". The rolled composite steel plate has a base layer of carbon steel and a composite layer of austenitic stainless steel. The thickness of the composite steel plate is no more than 10 mm. The inventor directly assembled the carbon steel slab and the austenitic stainless steel slab, and then hot-rolled and coiled to finally obtain the rolled composite plate coil. The thickness of the transition layer is mentioned in the patent, but the diffusion of elements in the transition layer and other related contents are not involved.

[0010] In summary of the above patents, in the existing rolled composite steel plate technology, there is little consideration of the transition layer at the interface between the base and the composite material, especially the influence of the diffusion of carbon elements in the base carbon steel material through the interface to the composite material on the corrosion resistance of the composite material under long-term high temperature conditions. Therefore, the technical solutions of these patents have not taken targeted measures to reduce the possibility of weakening the corrosion resistance of stainless steel due to the precipitation of carbides at the interface of the composite material. Especially in the chemical and energy industries, in many cases, the operating temperature of composite steel plate manufacturing equipment is in the range of 300-450℃. If it is operated at high temperature for a long time, the elements at the material interface may diffuse again, especially the carbon elements on the carbon steel side diffuse to the stainless steel composite layer, which will form more carbides, further reducing the corrosion resistance of stainless steel and forming accident hazards. Summary of the invention

[0011] The purpose of the present invention is to provide a corrosion-resistant rolled composite steel plate for medium-temperature equipment and a manufacturing method thereof, which can reduce the possibility of failure caused by intergranular corrosion of stainless steel on the composite side by blocking or reducing the diffusion of carbon elements on the carbon steel side of the substrate at the interface of the composite steel plate, and comprehensively improve the corrosion resistance and safety performance of the rolled composite steel plate. The composite steel plate is suitable for medium-temperature equipment at 300 to 450°C in energy manufacturing fields such as petroleum refining and coal chemical industry.

[0012] To achieve the above object, the technical solution of the present invention is:

[0013] The composite steel plate of the present invention forms a large number of MC (M represents one or more of V, Nb, and Ti) precipitation phases with fine and dispersed distribution and stable high-temperature performance in the base carbon steel. These stable carbide precipitation phases can fix the carbon element in the steel in the base carbon steel, thereby avoiding the diffusion and migration of the carbon element in the base to the transition layer near the bonding interface of the rolled composite steel plate under the working condition of 300-450°C, resulting in an increase in the carbon element concentration in the stainless steel near the interface, and a large number of carbide precipitation phases are generated at the stainless steel grain boundaries, inducing intergranular corrosion, and ultimately weakening or even losing the anti-corrosion function of the composite material.

[0014] Specifically, the corrosion-resistant rolled composite steel plate for medium-temperature equipment of the present invention comprises a substrate, a composite layer and a transition layer between the substrate and the composite layer, wherein the weight percentage of the components of the substrate is: C: 0.01% to 0.15%, Si: 0.2% to 0.7%, Mn: 0.1% to 1.70%, Ti: 0.006% to 0.025%, Als: 0.004% to 0.015%, Nb: 0.0010% to 0.050%, V: 0.15% to 0.50%, B: 0.0005% to 0.0050%, N: 0.0015% to 0.0050%, P≤0.0165%, S≤0.010%, O≤0.005%, and the balance includes Fe and other inevitable impurities;

[0015] The surface microstructure of the composite steel plate substrate is 60-80% bainite + 20-40% ferrite + MC precipitation phase; the central microstructure of the substrate is 30-40% bainite and 60-70% ferrite + MC precipitation phase; wherein M represents one or more of Nb, V, and Ti, the average major axis length of the MC precipitation phase is less than 500nm, and the volume density of the MC precipitation phase with a major axis size less than 500nm is greater than 2.0×10 4 Pieces / mm 3 ;

[0016] The composite steel plate is made of stainless steel, and its microstructure contains MC precipitated phase; wherein M represents one or more of Cr, Nb, Mo, and Ti, the average major axis length of the MC precipitated phase is less than 700 nm, and the volume density of the MC precipitated phase is less than 1.0×10 4 Pieces / mm 3 Preferably, the stainless steel is austenitic stainless steel, ferritic stainless steel, duplex stainless steel or super stainless steel.

[0017] Furthermore, the balance of the composition of the substrate is Fe and other inevitable impurities.

[0018] Furthermore, the substrate also contains at least one of the following chemical elements: 0<Ca≤0.0055%, 0<Ni≤0.65%, 0<Cu≤0.55%.

[0019] Preferably, in the composite steel plate substrate, the number ratio of MC precipitated phases with a major axis size of less than 500 nm to all MC precipitated phases is greater than 50%.

[0020] Preferably, in the composite layer of the composite steel plate, the MC precipitated phases with a major axis size of less than 700 nm account for more than 50% of the total MC precipitated phases.

[0021] Furthermore, there is a very small amount of σ phase in the multi-layer microstructure of the composite steel plate, and the proportion of the σ phase is ≤1.5%. Preferably, the proportion of the σ phase near the transition layer is ≤0.5%.

[0022] Preferably, the thickness of the base material of the composite steel plate is ≥6 mm, and the thickness of the composite layer is ≥2 mm; preferably, the thickness of the transition layer is ≤230 μm.

[0023] The yield strength of the base material of the composite steel plate of the present invention is ≥325MPa, the tensile strength is ≥430MPa, the cross-sectional shrinkage is ≥60%, the elongation is ≥19%, the -30°C impact absorption energy is ≥100J, and the -50°C impact absorption capacity is ≥45J; the grain size grade of the base material is not less than grade 7.0; the shear strength of the composite steel plate is ≥310MPa.

[0024] In the composition design of the composite steel plate substrate of the present invention:

[0025] C: C is an important strengthening element. In order to make the carbon steel plate have appropriate strength, it is necessary to control the mass percentage of C in the steel to be greater than or equal to 0.01%; at the same time, in order to improve the welding performance of the base carbon steel material, it is necessary to control the content of C in the carbon steel not to be too high. In addition, if the carbon content in the carbon steel substrate is high, due to the difference in the carbon concentration gradient of the two materials, a large-scale carbon migration will occur at the interface between the substrate and the stainless steel composite material, causing intergranular corrosion of the stainless steel. Therefore, the upper limit of the carbon element is controlled to be 0.15%. Accordingly, based on this, the present invention controls the C content to 0.01% to 0.15%.

[0026] Si: Similar to C, Si is also a strengthening element commonly used in low alloy steel. Adding a certain amount of Si to steel can improve the strength of steel. At the same time, Si also has a deoxidation function. During the smelting process, it can play an auxiliary deoxidation role. Most of the SiO2 products formed after deoxidation enter the steel slag and are removed, which will not affect the performance of the steel. In addition, adding a certain amount of Si to steel can reduce the solubility of carbon in austenite, thereby promoting carbon precipitation, promoting the formation of MC precipitation phase, fixing carbon in steel, and preventing large-scale diffusion of carbon. Therefore, a certain amount of Si needs to be added to the steel. However, excessive Si will reduce the welding performance of steel. Because Si has a stronger ability to bind oxygen than iron, it is easy to generate low-melting silicates during welding, increase the fluidity of slag and molten metal, cause splashing, and affect the quality of the welded joint. Therefore, controlling the content of Si within a certain range is helpful to improve the welding forming performance of steel. Therefore, the present invention controls the Si content to 0.2% to 0.7%.

[0027] Mn: Mn is also an important strengthening element, which can effectively improve the strength of the base steel plate. At the same time, the Mn element is an effective austenite stabilizing element. Adding a certain amount of Mn elements can increase the hardenability of steel. Therefore, in order to ensure the strength of steel, the lower limit of Mn is 0.1%. However, the Mn element is very easy to produce center segregation in steel. Excessive addition of Mn elements will cause serious segregation at the center of the thickness of the steel plate and reduce the low-temperature toughness of the core of the steel plate. Therefore, the upper limit of the Mn content can be limited to 1.7%. Based on this, the present invention controls the Mn content to 0.1% to 1.7%.

[0028] Ti: Ti is not only a deoxidizing element, but also a strong carbide-forming element and nitride-forming element. In the present invention, adding an appropriate amount of Ti element can, on the one hand, form a stable MC precipitation phase in the steel, fix the carbon element in the substrate, and prevent it from diffusing to the interface of the composite material. At the same time, part of the Ti element participates in fixing the free N element in the steel to form a TiN precipitation phase. The TiN precipitation phase can prevent the growth of austenite grains, refine the grains, and simultaneously improve the strength and toughness of the steel plate. After Ti fixes part of the free nitrogen element, it helps to ensure that the B element in the steel exists in the steel in a free state, thereby improving the hardenability of the steel. In addition, after Ti deoxidation, Ti2O3 particles can be formed to promote the formation of intracrystalline ferrite and improve the low-temperature impact toughness of the steel. However, when the Ti content in the steel is too high, the size of the TiN and Ti2O3 particles formed becomes larger, so that they no longer have the ability to hinder the growth of austenite and form intracrystalline ferrite. Instead, they will easily become the source of crack initiation, reducing the low-temperature impact toughness of the steel, so the upper limit of Ti is 0.025%. Based on this, the present invention controls the Ti content to 0.006% to 0.025%.

[0029] Als: Als is first of all an important deoxidizing element, which will form aluminum oxide inclusions. Moreover, the Al element can combine with the N element in the steel to form an AlN precipitation phase, which reduces the content of free N elements in the steel, thereby avoiding the combination of the B element in the steel with the N element, promoting the increase of the free B element content in the steel, improving the hardenability of the steel, and helping to improve the strength performance of the steel plate. However, when the acid-soluble aluminum content in the steel is too high, the size of its deoxidation product aluminum oxide will become larger, and because the aluminum oxide inclusions have a strong adsorption capacity, it will lead to the formation of large-sized aluminum oxide clusters. On the one hand, it will clog the water inlet during the steelmaking process and affect the pouring process of molten steel. If these large-sized clustered inclusions enter the steel plate, it will cause the inclusion rating and flaw detection of the steel plate to fail. Therefore, the present invention controls the Als content to 0.004% to 0.015%.

[0030] Nb: Nb is a strong carbide-forming element. Nb can combine with carbon in steel to form MC precipitation phase, stabilize carbon in steel, and prevent carbon from diffusing to the bonding interface. At the same time, adding an appropriate amount of Nb element can increase the recrystallization temperature of steel. After the steel is recrystallized and rolled in the austenite region, the austenite grains will not grow rapidly, and the strength and toughness of fine-grained steel are higher. However, when the Nb content in the steel is too high, the size of the MC precipitation phase formed will be larger, which will reduce the toughness of the steel plate and deteriorate the toughness of the heat-affected zone of the weld. Therefore, the present invention controls the Nb content to 0.0010% to 0.050%.

[0031] V: As a strong carbide-forming element, adding an appropriate amount of V can combine with free C in steel to form a stable VC precipitation phase, which can fix the carbon element in the steel. At the same time, the fine VC precipitation phase can have a precipitation strengthening effect and increase the strength of the steel plate. However, if too much V is added, excessive V will be dissolved in the ferrite matrix, thereby weakening the bonding force between atoms. Based on this, the V content is controlled at 0.15% to 0.50% in the present invention.

[0032] B: Adding an appropriate amount of B element is to make up for the fact that after the carbide fixes the carbon element, the content of solid dissolved carbon in the steel decreases, resulting in a decrease in the strength performance of the steel plate. If the B element in the steel exists in a free state, some of the B will preferentially occupy the grain boundary position, thereby improving the hardenability of the steel plate. The premise for it to work is that B must exist in the steel in a free state. Therefore, in order to prevent the B in the steel from combining with the oxygen and nitrogen elements to form boron oxide and boron nitride, the oxygen content and nitrogen content in the steel must be controlled, which is also the key point in the design of the alloy composition. However, it should be noted that if excessive B is added to the steel, too much B is prone to form a large amount of segregation at the grain boundaries, which will be detrimental to the toughness of the steel. Therefore, the present invention controls the B content to 0.0005% to 0.0050%.

[0033] N: In the present invention, appropriate amounts of Ti and Al elements are added during the design of the alloy composition. These two elements can form TiN and AlN precipitation phases with the N element in the steel. When these precipitation phases are fine and dispersed, they can refine the austenite grains, thereby improving the strength and toughness of the steel plate. However, when the N content in the steel is too high, the excess N element will combine with the B element in the steel to generate BN, consuming the free B element in the steel, reducing the effect of the B element on improving the strength of the steel plate. At the same time, too much N element will have an adverse effect on the toughness of the steel, especially when the solid solution N content exceeds 0.005%, the low-temperature toughness of the steel plate will be significantly reduced. Therefore, in the present invention, the N content is controlled to 0.0015-0.0050%.

[0034] The composite steel plate substrate of the present invention further contains at least one of the following chemical elements: 0<Ca≤0.0055%, 0<Ni≤0.65%, 0<Cu≤0.55%.

[0035] Ca: Ca is a strong deoxidizing element. Adding an appropriate amount of calcium can control the oxygen content in the steel, thereby preventing the oxidation of the B element. However, when the Ca content in the steel exceeds 0.0055%, large inclusions of calcium oxide and calcium sulfide are easily formed in the steel, which is detrimental to the toughness of the steel. Therefore, the present invention controls the Ca content to 0<Ca≤0.0055%.

[0036] Ni: Ni is a typical austenite stabilizing element, which can significantly improve the hardenability of the steel plate, and can also improve the low temperature toughness of the steel plate. However, the price of Ni is relatively high. Considering the production cost of steel, it is not appropriate to add excessive Ni to the steel. Therefore, the present invention controls the Ni content to 0<Ni≤0.65%.

[0037] Cu: Adding an appropriate amount of Cu element helps to improve the strength of steel and improve the corrosion resistance of steel. However, when the Cu content added to the steel is too high, the steel plate is prone to high-temperature brittleness at high temperatures. Therefore, the present invention controls the Cu content to 0<Cu≤0.55%.

[0038] It should be noted that the addition of the above-mentioned Ca, Ni and Cu elements will increase the production cost of the material. Taking into account the performance and cost control, in the technical solution of the present invention, at least one of the above-mentioned elements can be preferably added.

[0039] Inevitable impurities exist in the composite steel plate substrate of the present invention, with P≤0.0165%, S≤0.010%, and O≤0.005%.

[0040] P: P is a harmful element for most steel plates. The main reason is that P is very easy to segregate to the grain boundary, reducing the bonding force between atoms at the grain boundary, causing the temper brittleness of the steel plate, especially when the steel plate is working at high temperature, the temper brittleness of P will be aggravated. Therefore, the P content is controlled to P≤0.0165% in the present invention.

[0041] S: The S element in steel is very easy to combine with the Mn element in steel to form MnS inclusions. The higher the S content, the larger the size of the MnS formed, which is not good for the strength and toughness of the steel plate. At the same time, when the S content is too high, it will cause the center segregation of the slab and easily cause hot cracks. Therefore, the present invention controls the S content to S≤0.010%.

[0042] O: The oxygen element in steel basically exists in the form of oxides. When the O element content in steel is too high, it means that there are too many oxides in the steel, and large inclusions may exist, which affects the strength and toughness of the steel plate. Therefore, the present invention controls the O content to O≤0.005%.

[0043] The surface microstructure of the composite steel plate substrate of the present invention is 60-80% bainite + 20-40% ferrite + MC precipitation phase; the central microstructure of the substrate is 30-40% bainite and 60-70% ferrite + MC precipitation phase; the surface microstructure of the substrate is mainly bainite, supplemented by ferrite, mainly to ensure the strength and toughness of the substrate, especially when the steel plate is in service for a long time in the temperature range of 300-450°C, part of the free carbon elements that play a role in solid solution strengthening will be transformed into the second phase, and the surface strength of the substrate will be reduced. At this time, bainite strengthening can ensure that the material strength is maintained above the minimum strength of the material design. The increase in the proportion of ferrite in the central microstructure can further balance the problem of reduced material toughness caused by the segregation of the core of the continuous casting billet at the half of the plate thickness.

[0044] The substrate of the present invention has a stable MC precipitate phase, wherein M represents one or more of Nb, V, and Ti, and the average major axis length of the MC precipitate phase is less than 500 nm. When the size of the MC precipitate phase is too large, it is easy to have an adverse effect on the mechanical properties of the substrate, so it is necessary to control its average major axis length to be less than 500 nm. In the present invention, a carbide precipitate phase with a smaller size is formed in the substrate as much as possible to ensure that while the carbon fixation effect of the carbide is fully exerted, the mechanical properties of the steel plate will not be adversely affected by the precipitation of the carbide, so the number ratio of the MC precipitate phase with a major axis length less than 500 nm to all MC precipitates is limited to be greater than 50%.

[0045] Preferably, the volume density of the MC precipitated phase with a major axis length less than 500 nm in the substrate is greater than 2.0×10 4 Pieces / mm 3 In order to prevent the free carbon element from diffusing into the composite material, the free carbon element in the steel is fixed by forming a MC precipitation phase in the base steel plate of the present invention. Therefore, in the present invention, it is necessary to ensure that the volume density of MC is greater than 2.0×10 4 Pieces / mm 3 Only in this way can the carbon element in the steel be effectively controlled and the large-scale diffusion of free carbon elements to the stainless steel side be avoided.

[0046] The composite steel plate composite material of the present invention has a stable MC precipitation phase, wherein M represents one or more of Cr, Mo, Nb, and Ti, and the average major axis length of the MC precipitation phase is less than 700nm. The larger the size of the carbide in the composite material, the greater the impact on the corrosion resistance of the stainless steel. Therefore, it is hoped that the size of the carbide precipitation phase in the composite material is as small as possible. However, in the production process of the composite material and the rolled composite steel plate, some carbide precipitation phases will inevitably be generated. In order to ensure the corrosion resistance of the rolled composite steel plate, the present invention requires that the average major axis length of the MC precipitation phase in the composite material is less than 700nm.

[0047] The volume density of the MC precipitated phase in the composite material of the present invention is less than 1.0×10 4 Pieces / mm 3 From the perspective of controlling the amount of carbide precipitation phase in the composite material, it is hoped that the amount of carbides is as small as possible, that is, the smaller the volume density is, the better. However, some carbides will inevitably form during the heat treatment of the composite steel plate. The volume density of carbides is controlled to be less than 1.0×10 4 Pieces / mm 3 It can ensure the excellent corrosion resistance of the composite material.

[0048] Preferably, in the composite material of the present invention, the MC precipitate phase with a major axis length less than 700nm accounts for more than 50% of the total MC precipitate phase. In the present invention, the "volume density" of the MC precipitate phase is measured according to the method described in the YB / T 5320-2006 standard. In order to reduce the carbide precipitate phase in the composite material as much as possible to increase the corrosion resistance of the composite material, the size and number of the MC precipitate phase are limited in the present invention, that is, the MC precipitate phase with a major axis length less than 700nm accounts for more than 50% of the total MC precipitate phase. When the number and size of the carbide precipitate phase exceed the limit range, the corrosion resistance of the composite material will be greatly reduced, affecting the safe service performance of the rolled composite steel plate.

[0049] The composite layer of the present invention is stainless steel (austenitic stainless steel, ferritic stainless steel, duplex stainless steel, super stainless steel, etc.), and the σ phase in its microstructure is a metal phase with high hardness and low plasticity. When it precipitates along the grain boundary, it will have a great impact on the plasticity of the steel, resulting in a significant reduction in the impact toughness of the steel. Therefore, the σ phase ratio of stainless steel is ≤1.5%, especially the σ phase ratio near the bonding interface (transition layer) is ≤0.5%.

[0050] The present invention also provides a method for manufacturing a corrosion-resistant rolled composite steel plate for medium-temperature equipment, which comprises the following steps:

[0051] 1) Smelting and casting, preparation of base material and composite casting billet

[0052] According to the above components, the base material ingot is smelted and cast, and deoxidizers Mn+Si, Al, and Ti alloys are added to the molten steel for deoxidation during the smelting process; Mn+Si and Al are added in sequence for pre-deoxidation, and the oxygen level of the molten steel after pre-deoxidation is 0.0020% to 0.0075%, and then Ti is added for final deoxidation; after deoxidation, B element and other alloys are added, and then the base material ingot is cast by the top pouring method; at the same time, a stainless steel composite ingot is obtained;

[0053] 2) Assembly

[0054] The substrate ingot and the composite ingot are surface treated, and then overlapped, and the overlapped ingots are welded and sealed around the edges, vacuumed, and sealed again to form a composite ingot; preferably, after the vacuum is exhausted, the vacuum degree is 8 to 60 Pa;

[0055] 3) Composite slab rolling

[0056] The composite slab is heated to 1050-1220°C, and then rolled in two stages, the total reduction rate of the slab in the first stage is not less than 60%, the total reduction rate in the second stage is not less than 20%, the reduction rate of the last pass is 8-18%, the total reduction rate is not less than 80%, and the final rolling temperature is above 850°C;

[0057] 4) Heat treatment

[0058] The composite steel plate is subjected to quenching and tempering heat treatment.

[0059] Preferably, in step 2), the substrate and the composite cast slab are subjected to surface treatment to ensure that there are no obvious surface defects such as oil stains, slag inclusions, and cracks on the slab surface, and that the roughness of the slab processing surface is not greater than 2.0 Ra.

[0060] Preferably, in step 4), the quenching temperature is 935-975°C, the quenching holding time is T1=(1-1.2)H, and after the holding is completed, the steel plate is taken out of the furnace and cooled to room temperature with water, wherein T1 is in min, and H is the thickness of the steel plate in mm.

[0061] Preferably, in step 4), the tempering temperature is 650-725°C, the tempering holding time is T2=(1-1.5)H, and after the holding is completed, the steel plate is taken out of the furnace and cooled to room temperature with water, wherein T2 is in min, and H is the thickness of the steel plate in mm.

[0062] In the manufacturing method of the present invention,

[0063] A large amount of uniformly dispersed nano-scale MC precipitation phases need to be generated in the composite steel plate substrate of the present invention, and the MC precipitation phase is used to fix the free carbon element in the carbon steel substrate to prevent the carbon element from diffusing in large quantities to the interface between the substrate and the composite material, thereby causing the stainless steel to form carbides and reduce its corrosion resistance, thereby improving the service safety performance of the rolled composite steel plate for high-temperature equipment. However, the free carbon in the steel is a major strengthening element of the carbon steel substrate. When most of the free carbon elements are fixed in the form of MC, the strength of the carbon steel will decrease. In order to compensate for the strength loss after the carbon elements are fixed. It is necessary to add the B element to improve the hardenability of the steel plate. The hardenability of the B element mainly works through the distribution of free B at the grain boundary. Since the B element is an extremely active element, on the one hand, it can combine with the oxygen element in the molten steel to form boron oxide; on the other hand, the boron element is also easy to combine with the N element to form boron carbide. For this reason, in the technical solution of the present invention, the deoxidation sequence of the molten steel and the timing of adding the B element are specially designed. That is, during deoxidation, Si+Mn is used for pre-deoxidation, and most of silicon oxide and manganese oxide will float to the top slag. Using strong deoxidizer Al for deoxidation can more accurately control the oxygen level (determined according to the method for measuring oxygen content in molten steel recorded in ISO 14284:1996 standard) at 0.0020% to 0.0075%, and then Ti is used for final deoxidation to form a large amount of Ti oxide. At the same time, the added Ti can combine with the free nitrogen element in the steel to form TiN. That is, the addition of Ti element will further reduce the free oxygen concentration in the steel. Within a certain oxygen position range (0.0020% to 0.0075%), the size of the Ti2O3 inclusions formed after deoxidation is appropriate (2-5μm), which is conducive to the formation of part of the acicular ferrite structure during solidification and subsequent phase transformation, and improves the toughness of the steel plate. In addition, Ti element can also combine with N element in steel to generate part of TiN, which can reduce the adverse effect of solid solution nitrogen on the toughness of steel on the one hand, and on the other hand, TiN can precipitate at high temperature during solidification, play a role in pinning the growth of austenite, and refine the original austenite grains. When the oxygen and titanium elements in the steel are controlled in place, an appropriate amount of B element is added, thereby ensuring that the added B element is mainly present in the steel in a free state, ensuring that the base steel plate has a high hardenability, and can significantly improve the strength of the steel plate.

[0064] In step 3), the composite slab is heated to 1050-1220°C for rolling because: when the heating temperature is less than 1050°C, the carbides and nitrides in the base material ingot cannot be completely dissolved, which will reduce the pinning effect of the carbides on the austenite grains during the rolling process; at the same time, within this temperature range, it is conducive to the homogenization of the austenite of the composite material, and the carbides in the composite material are also completely dissolved. When the heating temperature of the ingot is higher than 1220°C, it is easy to cause the rapid growth of the austenite grains of the base material and the composite material, which will damage the mechanical properties of the steel.

[0065] Accordingly, it is preferred that the total reduction rate of the slab in the first stage of rolling is not less than 60%, the total reduction rate in the second stage of rolling is not less than 20%, the reduction rate of the last pass is 8-18%, the total cumulative reduction rate of rolling is not less than 80%, and the final rolling temperature is above 850°C.

[0066] Through the first stage of high-temperature and high-reduction rolling, the material can be fully recrystallized during the rolling deformation process, the austenite grains can be continuously refined, and the formation of larger austenite grains in the steel can be inhibited, thereby improving the low-temperature toughness of the steel. When the total reduction rate in the first stage is less than 60%, the austenite grain size in the steel is larger, which is not conducive to the strength and toughness indicators of the steel plate.

[0067] The total reduction rate of the second stage rolling is not less than 20%, which can further promote the refinement of austenite grains. The final rolling pass reduction rate is 8-18%, which can increase the dislocation density in the steel and ensure the strength of the steel plate. When the reduction rate is lower than 8%, the dislocation density is low, which is not conducive to strength improvement. When the reduction rate is higher than 18%, the rolling torque is too large, which is not conducive to the rolling equipment. When the final rolling temperature is lower than 850℃, the deformation resistance of the steel plate increases, and it is difficult to ensure a larger final rolling reduction rate.

[0068] In step 4), the quenching temperature is 935-975°C, the quenching holding time is T1=(1-1.2)H, and after the holding is completed, the steel is taken out of the furnace and water-cooled to room temperature, wherein T1 is in min, and H is the thickness of the steel plate in mm.

[0069] It should be noted that during the quenching process, when the quenching temperature is lower than 935°C, the homogenization of the austenite of the steel takes a long time, which will reduce the efficiency of the heat treatment; and if the quenching temperature of the steel is higher than 975°C, part of the austenite in the carbon steel tends to grow and is easy to form a mixed crystal structure, which is not conducive to the uniformity of the steel structure. Accordingly, when the holding time T1 of the steel at the quenching temperature is less than 1H, it cannot be fully austenitized, and when the holding time T1 of the steel exceeds 1.2H, it will exceed the time required for the austenitization of the steel, which will reduce the efficiency of the quenching process.

[0070] In step 4), the tempering temperature is 650-725°C, the tempering holding time is T2=(1-1.5)H, and after the holding is completed, the steel is taken out of the furnace and water-cooled to room temperature, wherein T2 is in min, and H is the thickness of the steel plate in mm.

[0071] During the tempering process, when the tempering temperature of the steel is lower than 650℃, a longer tempering time is required to remove the residual quenching stress in the steel, which will reduce the tempering efficiency and the formation rate of MC precipitation phase in carbon steel will be slower; when the tempering temperature of the steel is higher than 725℃, the MC precipitation phase in the steel is prone to Ostwald coarsening and aggregation and growth, which is not conducive to the formation of fine and dispersed MC precipitation phase in the steel. Correspondingly, when the tempering holding time T2 is lower than 1H, the quenching stress of the steel tends to not be completely removed, and when the tempering holding time T2 is higher than 1.5H, the MC precipitation phase in the steel is prone to coarsening and will reduce the production efficiency of the tempering process.

[0072] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows:

[0073] 1. The present invention forms fine and dispersed spherical (2-5 μm) Ti2O3 oxides in steel as nucleation cores for MC carbide precipitation phases. Combined with the design of alloy composition optimization and heat treatment process design, a large number of dispersed and distributed nano-scale MC (M represents one or more of V, Nb, and Ti) precipitation phases can be formed in the substrate, which can fix the free carbon element in the substrate, reduce the diffusion and aggregation of carbon elements to the composite interface, reduce the precipitation of stainless steel grain boundary carbides, and ensure the corrosion resistance of the composite rolled steel plate. In particular, when the rolled composite steel plate is used in high-temperature equipment, under high-temperature working conditions of 300 to 450°C, the high-melting-point Ti2O3 oxide (melting point of 2130°C) formed by controlling the smelting process can still stably exist in the steel and continue to play a role as the precipitation core of MC carbides. That is, some of the free carbon elements in the steel can still react with the alloy elements in the steel with Ti2O3 oxide as the nucleation core to form fine MC carbides, thereby further fixing the carbon elements, ensuring that the carbon elements in the carbon steel do not diffuse to the interface, and protecting the corrosion resistance of the rolled composite steel plate under long-term high-temperature service.

[0074] 2. In the existing production process of low-alloy high-strength steel, the steel quality is purified, and aluminum is often used as a deoxidizer for deoxidation to reduce the oxygen content in the steel as much as possible. The advantage of aluminum deoxidation is its high deoxidation efficiency. Its disadvantage is that after aluminum deoxidation, the Al2O3 inclusions formed in the molten steel are likely to have an adverse effect on the flaw detection and performance of the steel plate. This is mainly because single Al2O3 inclusions are mostly angular and easy to form crack sources in the steel; at the same time, Al2O3 inclusions are very likely to aggregate in the molten steel, forming large-sized Al2O3 inclusion clusters that block the pouring nozzle. When large-sized inclusions exist in the steel, the tensile and impact properties of the steel plate are very likely to fluctuate. In addition, Al2O3 inclusions cannot serve as the nucleation core of the carbide precipitation phase.

[0075] In the present invention, by controlling the type of deoxidizer, the order of deoxidation and the amount of deoxidizer added during the steel smelting process, a spherical (2-5 μm) Ti2O3 oxide with a high melting point and fine dispersion distribution is finally formed in the steel. Ti2O3 oxide is not easy to aggregate and grow in the molten steel, has no edges and corners, has no obvious damage to the flaw detection and mechanical properties of the steel plate, and can optimize the organization type of the steel plate; by controlling the element content ratio, TiN precipitation is controlled, and the austenite grains are refined; by designing the order of adding steel alloys, the oxidation and nitridation of the B element can be effectively reduced, so as to make full use of the added B element, maximize the hardenability of the steel plate, refine the grains, and ensure that the steel plate has high strength and excellent low-temperature toughness.

[0076] In addition, through the preferred smelting process control, especially through the control of the deoxidizer type, deoxidation sequence and deoxidizer addition amount, the fine and dispersed spherical (2-5μm) Ti2O3 oxide formed in the steel can serve as the nucleation core of the MC carbide precipitation phase. Combined with the design of the alloy composition optimization and the design of the heat treatment process, a large number of dispersed and distributed nano-scale MC (M represents one or more of V, Nb, Ti) precipitation phases can be formed in the substrate, which can fix the free carbon element in the substrate, reduce the diffusion and aggregation of carbon elements to the composite interface, reduce the precipitation of stainless steel grain boundary carbides, and ensure the corrosion resistance of the composite rolled steel plate. In particular, when the rolled composite steel plate is used for high-temperature equipment, under the high-temperature working conditions of 300℃ to 450℃, the high-melting-point Ti2O3 oxide (melting point is 2130℃) formed by controlling the smelting process can still stably exist in the steel and serve as the precipitation core of MC carbides and continue to play a role. That is, some of the free carbon elements in the steel can still react with the alloy elements in the steel with Ti2O3 oxide as the nucleation core to form fine MC carbides, thereby further fixing the carbon elements, ensuring that the carbon elements in the carbon steel do not diffuse to the interface, and protecting the corrosion resistance of the rolled composite steel plate under long-term high-temperature service.

[0077] The composite steel plate of the present invention has excellent corrosion resistance and can be effectively used in the energy and chemical industry as a manufacturing material for high-temperature reaction vessels at 300 to 450° C. It has very important practical significance and a very broad application prospect. DETAILED DESCRIPTION

[0078] The present invention will be further described below in conjunction with specific embodiments. However, this description does not constitute an improper limitation on the technical solution of the present invention.

[0079] The composition of the embodiment of the present invention is shown in Table 1, and the remainder includes Fe and other inevitable impurities. The composite material of the rolled composite steel plate in the embodiment of the present invention and the comparative example is described by taking austenitic stainless steel as an example. The manufacturing process parameters of the embodiment of the present invention are shown in Table 2.

[0080] The manufacturing method of the embodiment of the present invention comprises the following steps:

[0081] 1) Smelting and casting: smelting and continuous casting are carried out according to the chemical composition shown in Table 1 to obtain a casting billet; the smelting equipment adopts a 500Kg vacuum induction furnace; first, 410kg of industrial pure iron is added to the vacuum induction furnace, and a certain amount of CaO is added with the furnace according to the alloy composition ratio of the steel (the added CaO is used for slag making during smelting); vacuum is drawn, and smelting is carried out at a vacuum degree of about 25Pa at the lowest, and argon gas is required for atmosphere protection during the smelting process; after the pure iron is melted, deoxidizers Si+Mn and Al are added in sequence for pre-deoxidation, and according to the online monitoring results of the molten steel composition, the amount of deoxidizer added is finely adjusted and the oxygen level of free oxygen in the molten steel is controlled to be 0.0020% to 0.0075%, and then an appropriate amount of Ti is added for final deoxidation; alloys such as Nb and V are added for alloying treatment, and finally B is added, and the ingot is cast by the top pouring method;

[0082] 2) Assembly: Process the surfaces of the base carbon steel slab and the composite stainless steel slab. The roughness of the butt surface of the two materials is ≤2.0Ra. After surface inspection, ensure that there are no surface defects such as oil stains, slag inclusions, cracks, etc. After welding around the slab, vacuum is drawn with a vacuum degree of 8-60Pa.

[0083] 3) rolling, heating the composite slab at 1050-1220°C, and then performing two-stage rolling, the total reduction rate of the slab in the first stage is not less than 60%, the total reduction rate in the second stage is not less than 20%, the reduction rate of the last pass is 8-18%, the total reduction rate is not less than 80%, and the final rolling temperature is above 850°C;

[0084] 4) Heat treatment, quenching and tempering the rolled composite steel plate; quenching the composite rolled steel plate, the quenching temperature is 935-975°C, the quenching holding time T1 is 1-1.2H, after the holding is completed, it is taken out of the furnace and water-cooled to room temperature; then tempering treatment is performed, the tempering temperature is 650-725°C, the tempering holding time T2 is 1-1.5H, and air cooling is performed after taking out of the furnace; wherein H represents the thickness of the steel plate, in mm.

[0085] In the present invention, the chemical composition design and related processes of the composite steel plate substrates of Examples 1 to 7 all meet the design specification requirements of the present invention.

[0086] In contrast, the rolled composite steel plates of Comparative Examples 1 to 3 are manufactured using the same process steps as Example 1, except that: the alloy element content of the base carbon steel of Comparative Examples 1 to 2 exceeds the design range, and the alloy range of the base carbon steel of Comparative Example 3 is within the design range, but in the smelting and pouring operations of the above step (1), the order of adding the deoxidizer and the B alloy in Comparative Examples 1 to 3 is different; and the heat treatment and tempering processes are different.

[0087] Electrolytic samples were taken from the base carbon steel material and the composite stainless steel of the composite steel plates of Examples 1 to 7 and the control rolled composite steel plates of Comparative Examples 1 to 3. The MC precipitated phase in the stainless steel was extracted by electrolytic extraction, and the precipitated phases of different scale ranges were separated by filter membranes of different particle sizes; the particle size distribution of the precipitated phase was detected by a laser particle size analyzer, and the number and size distribution range of the MC precipitated phase (M represents one or more of Nb, V, Ti, and Cr) in the steel plates of each embodiment and comparative example were finally confirmed by using image analysis software, and the data obtained by observation and analysis were finally listed in Table 3 (base material) and Table 4 (composite material at the bonding interface).

[0088] As can be seen from Table 3, the total number of precipitated phases in the carbon steel material of the base material of the rolled composite steel plate of Examples 1-7 is 582 to 791, which is much higher than the 340 to 432 of the carbon steel material of the base material of the comparative example, indicating that after the implementation of the technical solution of the present invention, a larger number of MC carbide precipitation phases can be formed in the base carbon steel material, thereby ensuring the effect of fixing the free carbon in the carbon steel by the stable carbides in the base carbon steel designed in the technical solution. Moreover, the size of the MC precipitation phase in the carbon steel material of the base material of the rolled composite steel plate of Examples 1-7 is relatively small, and their main distribution range is 200 to 600 nm. The average major axis length of the MC precipitation phase is less than 500 nm, and the volume density of the MC precipitation phase is greater than 2.0×10 4 Pieces / mm 3 The MC precipitates with a size less than 500nm account for more than 50% of the total MC precipitates. When the precipitates are small in size, they can play a role in pinning the growth of austenite grains to a certain extent, thereby refining the grains and further improving the strength and toughness of the material.

[0089] However, the size of the MC precipitated phase in the carbon steel of the rolled composite steel plate substrate of Comparative Examples 1-3 is relatively large, the average major axis length of the MC precipitated phase is greater than 800nm, the size distribution range of the main precipitated phase is above 800nm, and the proportion of precipitated phases above 1000nm is relatively high, which has a poor pinning effect on austenite grains, resulting in a larger grain size, affecting the strength and toughness of the steel plate. Since the number of stable precipitated phases formed in the carbon steel material of the comparative example is small, the amount of free carbon fixed in the precipitated phase relative to the carbon steel is reduced, resulting in a large amount of free carbon being segregated to the bonding interface, thereby generating a large amount of carbides precipitated from grain boundaries at the composite material of the bonding interface, reducing the corrosion resistance of the composite material at the interface.

[0090] As shown in Table 4, in the composite material of the composite steel plates of Examples 1-7 located near the transition layer, the number of MC precipitates detected is 146-182, which is much less than 403-411 in the comparative example, and the volume density of the MC precipitates in the composite material at the interface (transition layer) of the embodiment is less than 1×104 Pieces / mm 3 . This shows that the amount of carbon in the base carbon steel material of Examples 1-7 that diffuses into the composite material through the interface is small, and the amount of MC formed is small, while in Comparative Examples 1-3, a large amount of carbon in the carbon steel material diffuses into the composite material through the interface, resulting in a large amount of carbides in the corresponding composite material. At the same time, it can be seen from Table 4 that in the composite material at the interface (transition layer) of Examples 1-7, the average major axis length of the MC precipitation phase is less than 700nm, and the MC precipitation phase with a size less than 700nm accounts for more than 50% of the total MC precipitation phase; correspondingly, the average size of the MC precipitation phase obtained by inspection in the comparative example is greater than 900nm. This also further illustrates that the carbide fixation effect on free carbon in the examples is much better than that in the comparative example.

[0091] After analyzing the carbide precipitation phases of the composite steel plates of Examples 1 to 7 and the steel plates of Comparative Examples 1 to 3, the mechanical properties and corrosion resistance of the steel plates of Examples 1 to 7 and Comparative Examples 1 to 3 were also evaluated. The evaluation results are shown in Table 5. As can be seen from Table 5, the yield strength and tensile strength of the carbon steel substrate of the comparative example are lower than those of the embodiment. The main reason is that the smelting process, alloy addition sequence and heat treatment process of the carbon steel of the comparative example substrate are different from those of the embodiment, thereby causing the hardenability of the B element in the comparative steel to not fully play its role, and the precipitation phases in the steel are different, which has different effects on the microstructure of the steel plate. The surface microstructure of the composite steel plate substrate of the present invention is 60-80% bainite + 20-40% ferrite + MC precipitation phase, and the central microstructure of the substrate is 30-40% bainite and 60-70% ferrite structure + MC precipitation phase. The smaller precipitated phases in the embodiment further refine the austenite grains, which plays a certain role in improving the strength and toughness of the steel plate.

[0092] The stainless steel near the bonding interface (transition layer) of the rolled composite steel plates of the embodiment and the comparative example was subjected to intergranular corrosion test according to ASTMA262 practice E method. The test results are shown in Table 6. From the results, it can be seen that the stainless steel at the bonding interface of the rolled composite steel plate prepared according to the technical requirements of the present invention has excellent corrosion resistance. Therefore, among the composite steel plates of Examples 1 to 7, the corrosion resistance of the composite stainless steel plates of each embodiment is far better than that of the comparative example.

[0093] In summary, the composite steel plate of the present invention can be produced by reasonable chemical composition design and optimized production process, especially by controlling the type of deoxidizer, deoxidation sequence and the amount of deoxidizer added in the steel smelting process, and alloying treatment can be performed in a certain order, so that a large number of dispersedly distributed nano-scale MC (M represents one or more of Nb, V, Ti, Cr) precipitation phases can be generated in the steel. These nano-scale MC precipitation phases can fix the free carbon elements in the base carbon steel, thereby preventing these carbon elements from diffusing in large quantities to the bonding interface (transition layer), resulting in the formation of a large number of carbide precipitation phases in the stainless steel at the bonding interface, causing the corrosion resistance of the stainless steel to decrease. Therefore, the use of the technical solution of the present invention can ensure the strength and toughness of the carbon steel substrate, and at the same time can greatly improve the corrosion resistance of the rolled composite steel plate.

[0094] In addition, it should be noted that the combination of the various technical features in this case is not limited to the combination described in the claims of this case or the combination described in the specific embodiments. All technical features recorded in this case can be freely combined or combined in any way unless there is a contradiction between them.

[0095] It should also be noted that the above-listed embodiments are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and similar changes or modifications made therewith can be directly derived or easily associated with by those skilled in the art from the contents disclosed in the present invention, and all should belong to the protection scope of the present invention.

[0096]

[0097]

[0098]

[0099]

[0100]

[0101]

Claims

1. A corrosion-resistant rolled composite steel plate for medium-temperature equipment, comprising a substrate, a composite layer and a transition layer between the substrate and the composite layer, wherein the weight percentage of the components of the substrate is: C: 0.01% to 0.15%, Si: 0.2% to 0.7%, Mn: 0.1% to 1.70%, Ti: 0.006% to 0.025%, Als: 0.004% to 0.015%, Nb: 0.0010% to 0.050%, V: 0.15% to 0.50%, B: 0.0005% to 0.0050%, N: 0.0015% to 0.0050%, P≤0.0165%, S≤0.010%, O≤0.005%, the balance includes Fe and other unavoidable impurities; The surface microstructure of the composite steel plate substrate is 60-80% bainite + 20-40% ferrite + MC precipitation phase; the central microstructure of the substrate is 30-40% bainite and 60-70% ferrite + MC precipitation phase; wherein, M represents one or more of Nb, V, and Ti, the average major axis length of the MC precipitates is less than 500 nm, and the volume density of the MC precipitates with a major axis length less than 500 nm is greater than 2.0×10 4 Pieces / mm 3 ; The composite steel plate is made of stainless steel, and its microstructure contains MC precipitated phase; wherein M represents one or more of Cr, Nb, Mo, and Ti, the average major axis length of the MC precipitated phase is less than 700 nm, and the volume density of the MC precipitated phase is less than 1.0×10 4 Pieces / mm 3 ; Preferably, the stainless steel is austenitic stainless steel, ferritic stainless steel, duplex stainless steel or super stainless steel.

2. The corrosion-resistant rolled composite steel plate for medium-temperature equipment according to claim 1, characterized in that: The balance of the composition of the substrate is Fe and other inevitable impurities.

3. The corrosion-resistant rolled composite steel plate for medium temperature equipment according to claim 1 or 2, characterized in that: The substrate further contains at least one of the following chemical elements: 0<Ca≤0.0055%, 0<Ni≤0.65%, 0<Cu≤0.55%.

4. The corrosion-resistant rolled composite steel plate for medium temperature equipment according to claim 1, 2 or 3, characterized in that: In the composite steel plate substrate, the MC precipitated phases with a major axis length of less than 500 nm account for more than 50% of the total MC precipitated phases.

5. The corrosion-resistant rolled composite steel plate for medium temperature equipment according to claim 1, 2, 3 or 4, characterized in that: In the composite layer of the composite steel plate, the MC precipitated phase with a major axis length less than 700 nm accounts for more than 50% of the total MC precipitated phase.

6. The corrosion-resistant rolled composite steel plate for medium temperature equipment according to claim 1, 2, 3, 4 or 5, characterized in that: There is also a very small amount of σ phase in the multi-layer microstructure of the composite steel plate, and the proportion of the σ phase is ≤1.5%. Preferably, the proportion of the σ phase near the transition layer is ≤0.5%.

7. The corrosion-resistant rolled composite steel plate for medium temperature equipment according to claim 1, 2, 3, 4, 5 or 6, characterized in that: The thickness of the base material of the composite steel plate is ≥6 mm, and the thickness of the composite layer is ≥2 mm; preferably, the thickness of the transition layer is ≤230 μm.

8. The corrosion-resistant rolled composite steel plate for medium temperature equipment according to claim 1, 2, 3, 4, 5, 6 or 7, characterized in that: The yield strength of the base material of the composite steel plate is ≥325MPa, the tensile strength is ≥430MPa, the cross-sectional shrinkage is ≥60%, the elongation is ≥19%, the -30°C impact absorption energy is ≥100J, and the -50°C impact absorption capacity is ≥45J; the grain size grade of the base material is not less than grade 7.0; the shear strength of the composite steel plate is ≥310MPa.

9. The method for manufacturing a corrosion-resistant rolled composite steel plate for medium-temperature equipment according to any one of claims 1 to 8, characterized in that: The steps include: 1) Smelting and casting, preparation of base material and composite casting billet According to the composition of claim 1, 2 or 3, the base material ingot is smelted and cast, and deoxidizers Mn+Si, Al, and Ti alloys are added to the molten steel for deoxidation during the smelting process; Mn+Si and Al are added in sequence for pre-deoxidation, and the oxygen level of the molten steel after pre-deoxidation is 0.0020% to 0.0075%, and then Ti is added for final deoxidation; after deoxidation, B element and other alloys are added, and then the base material ingot is cast by the top pouring method; at the same time, a stainless steel composite ingot is obtained; 2) Assembly The substrate ingot and the composite ingot are surface treated, and then overlapped, and the overlapped ingots are welded and sealed around the edges, vacuumed, and sealed again to form a composite ingot; preferably, after the vacuum is exhausted, the vacuum degree is 8 to 60 Pa; 3) Composite slab rolling The composite slab is heated to 1050-1220°C, and then rolled in two stages, the total reduction rate of the slab in the first stage is not less than 60%, the total reduction rate in the second stage is not less than 20%, the reduction rate of the last pass is 8-18%, the total reduction rate is not less than 80%, and the final rolling temperature is above 850°C; 4) Heat treatment The composite steel plate is subjected to quenching and tempering heat treatment.

10. The method for manufacturing the corrosion-resistant rolled composite steel plate for medium-temperature equipment according to claim 9, characterized in that: In step 2), the substrate and the composite ingot are surface treated to ensure that there are no obvious oil stains, slag inclusions, cracks or other surface defects on the surface of the ingot, and that the roughness of the processed surface of the ingot is not greater than 2.0 Ra.

11. The method for manufacturing the corrosion-resistant rolled composite steel plate for medium-temperature equipment according to claim 9, characterized in that: In step 4), the quenching temperature is 935-975°C, the quenching holding time is T1=(1-1.2)H, and after the holding is completed, the steel is taken out of the furnace and water-cooled to room temperature, wherein T1 is in min, and H is the thickness of the steel plate in mm.

12. The method for manufacturing the corrosion-resistant rolled composite steel plate for medium-temperature equipment according to claim 9 or 11, characterized in that: In step 4), the tempering temperature is 650-725°C, the tempering holding time is T2=(1-1.5)H, and after the holding is completed, the steel is taken out of the furnace and water-cooled to room temperature, wherein T2 is in min, and H is the thickness of the steel plate in mm.

Citation Information

Patent Citations

  • Copper / aluminum composite belt manufacturing method capable of thinning boundary layer

    CN103934266A

  • High-strength and anti-corrosion composite pattern steel and manufacturing method thereof

    CN108085585A

  • Superaustenitic stainless steel rolled composite steel plate and manufacture method thereof

    CN108116006A